Food system futures in Finland: How do experts evaluate changes in resilience up to 2030? - Rikkonen, Pasi; Rimhanen, Karoliina; Aro, Kalle (Elsevier BV, 2024)
Food security has received much attention since sudden shocks like Covid-19 and the Russian invasion of Ukraine. Resilience to sudden changes and disruptions is called for to maintain food availability in societies. In this study, potential disruptions and changes in the Finnish food system’s operating environment were evaluated. We focused on two future challenges: 1) what key disruptions will confront the food system until 2030; and 2) how will the Finnish food system change based on the experts’ views, and what measures will develop resilience up to 2030? We used the Delphi technique for data gathering. According to the results, the most significant shock at all three levels, national, EU, and global, was the disruptions caused by climate change (the increase in extreme climate and weather phenomena). An increase in the efficient recycling of nutrients was seen as most desirable, and an increase in the costs associated with recovery from disturbances and shocks was seen as most likely. Reducing inputs’ dependence on imports was seen as a key measure for developing resilience. Two constructed scenarios were presented, which highlight the determinants and uncertainties in the development of resilience in Finland.
Keywords: Agriculture; Food system; Delphi method; Resilience; Scenario planning